Teacher Strategies In Addressing Disruptive Student Behavior In Class (Case Study of Cijati State Elementary School, Cijati Village, Maniis District) - Zeni Raziah Puspita Sari; Amit Saepul Malik; Dede Supriyatna (Manajia: Journal of Education and Management, 2026)
This study aims to describe teacher strategies in addressing disruptive student behavior in elementary school classrooms. The research employed a qualitative approach using a case study method conducted at Cijati State Elementary School. The research subjects consisted of classroom teachers and students. Data were collected through interviews, observations, and documentation. The findings indicate that teachers implement several strategies to manage disruptive student behavior, including preventive strategies through the establishment of clear classroom rules, intervention strategies in the form of warnings and educational consequences, and restorative strategies through communication and personal guidance. In addition, disruptive behavior is influenced by internal factors such as low learning motivation and emotional problems, as well as external factors including family environment and peer influence. This study is expected to contribute to the development of effective and conducive classroom management practices.